2022
DOI: 10.3390/cells11182867
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cardiovascular Disease-Related Genes Based on the Co-Expression Network Analysis of Genome-Wide Blood Transcriptome

Abstract: Inference of co-expression network and identification of disease-related modules and gene sets can help us understand disease-related molecular pathophysiology. We aimed to identify a cardiovascular disease (CVD)-related transcriptomic signature, specifically, in peripheral blood tissue, based on differential expression (DE) and differential co-expression (DcoE) analyses. Publicly available blood sample datasets for coronary artery disease (CAD) and acute coronary syndrome (ACS) statuses were integrated to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Kwon et al [30] reported a subset of paracrine factors, such as VEGF, MCP1, and IL6, as stem-cell-therapy-related markers. MSCs encompass a novel secretome network that cannot be substituted by single chemokine agents [45]; therefore, co-expression network analysis or deep learning is required to discover MSC-prognosis-related biomarkers [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kwon et al [30] reported a subset of paracrine factors, such as VEGF, MCP1, and IL6, as stem-cell-therapy-related markers. MSCs encompass a novel secretome network that cannot be substituted by single chemokine agents [45]; therefore, co-expression network analysis or deep learning is required to discover MSC-prognosis-related biomarkers [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al [52] recently analyzed the mRNAs of all genes isolated from BM-MSCs and identified several therapy-response-related genes. Moreover, we previously established an analytical platform for transcriptome data based on a co-expression network [47], which can be used in future studies to determine molecular signatures related to the identity and therapeutic effects of MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have shown that moderately increased albuminuria (UACR < 30 mg/g) within the accepted normal range is associated with higher cardiovascular morbidity and mortality, even in the general population 3 , 4 . Cardiovascular disease (CVD) is a broad-spectrum disease associated with numerous pathophysiological mechanisms such as inflammation 5 , fatty acid metabolic processes, and cholesterol metabolic process 6 .…”
Section: Introductionmentioning
confidence: 99%